Comparison of Mean Time to Regression of Sensory Block in Patients Treated with Sequential Combined Spinal Epidural Anesthesia Vs. Epidural Volume Extension in Patients Undergoing Lower Limb Surgeries - Khan , Muhammad Bilal Hussain; Sikander, Rana Imran; Fatima, Naheed; Amir , Asna; Bokhari , Farzana Mazhar; Ahmed, Danial (Indus Journal of Bioscience Research, 2025)
Background: It is now well established that these lower limb surgeries often use techniques of regional anesthesia that include Sequential Combined Spinal Epidural Anesthesia (SCSE) and Epidural Volume Extension (EVE). Both techniques provide effective sensory blockade but there remains interest in the relative effect on sensory regression time, hemodynamic stability, analgesic duration. Objective: This study aims to compare SCSE and EVE in terms of mean time to sensory regression, hemodynamic stability, and postoperative analgesia in lower limb surgeries. Results: A randomized controlled trial was conducted at the Department of Anesthesiology, Shaheed Zulfiqar Ali Bhutto University of Medical Sciences (PIMS) Islamabad during a period of six months. Sixty patients (ASA I–ll), who were undergoing lower limb surgeries, were randomly allocated to the SCSE and EVE group. The variables included sensory regression time to T12, hemodynamic parameters and duration of analgesia, which were analyzed using SPSS version 26.0. Conclusions: EVE had a significantly longer sensory regression time (120 ± 17.39 min) versus SCSE (98 ± 15.35 min; p=0.000). The EVE group had greater hemodynamic stability with fewer patients experiencing significant fluctuations in heart rate and systolic blood pressure compared to the SCSE group. Analgesia was comparable between both the techniques with duration of analgesia (143 min in EVE vs 134 min in SCSE, p=0.104). EVE allows a prolonged sensory blockade with superior continued hemodynamic stability, which makes it the better option for patients with risk of hypotension. However, SCSE continues to provide a sensible option where a very rapid, profound anesthesia is necessary. These findings need further validation in multiple centers and wider application.